Vector Vortex Beam-Enabled Edge Microscopy with Dynamic Orientation Selectivity - Hammad Ahmed (7526297) (2025)
Edge enhancement is an image processing technique that aids in highlighting structural details, especially in samples with weak scattering properties or low intrinsic contrast. While traditional methods such as scalar vortex-based filtering provide isotropic edge detection, they lack orientation selectivity and often introduce artifacts when modified for anisotropic imaging. Here, we present a multifunctional edge imaging system based on vector vortex beams that can be used for dynamic polarization control for orientation-selective edge enhancement. The system integrates a metasurface (Vector Vortex beam) VVB generator within a 4f Fourier transform configuration, along with a pair of rotating half-wave plates that enable tunable spatial polarization distributions. This configuration allows real-time visualization of edge features aligned along specific orientations. We demonstrate the effectiveness of this approach through experiments on resolution charts and label-free imaging of Saccharomyces cerevisiae yeast cells. The ability to selectively highlight edge features with dynamic control makes our system a powerful tool for high-contrast, orientation-resolved imaging in microscopy, biomedical diagnostics, and optical inspection.